Evaluasi Pengaruh DAR, ROA, Dan Kepemilikan Institusional Terhadap Tax Avoidance Dengan Kinerja Keuangan Sebagai Variabel Pemoderasi - Natrion; Lina Royani; Tagor Darius Sidauruk; Heriston Sianturi (Jurnal Liabilitas, 2026)
This study analyzes the role of institutional ownership, return on assets (ROA), and the debt to asset ratio (DAR) in influencing tax avoidance, and further explores the moderating role of corporate financial performance in property firms listed on the Indonesia Stock Exchange (IDX) throughout the 2020–2024 period. A quantitative approach is employed as the study method by utilizing document-based secondary data in the form of annual financial reports from 11 property companies that meet the purposive sampling criteria. Multiple linear regression analysis is applied to examine the data with financial performance incorporated as a moderating variable. The partial test results indicate that institutional ownership and ROA affect tax avoidance practices, whereas the debt to asset ratio (DAR) does not have a statistically significant effect. Moreover, financial performance is found to amplify the linkage between institutional ownership, ROA, and DAR in explaining tax avoidance practices among property sector firms.